Analisis Pengaruh Kualitas Pelayanan Publik terhadap Kepuasan Masyarakat - Awaliyah Matondang, Khairani; Nurita Pasaribu; Venus Situmeang; Rasmita Tarigan, Desry (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The comparison between the actual service received and the expectations of the desired service forms a very crucial concept of service quality. Service quality plays an important role in ensuring public satisfaction. This research aims to determine the impact of the quality of public services on the level of community satisfaction. The method applied in this research is literature review, literature review is used to collect and evaluate related research. Villages in Indonesia were selected as the research population. Based on a literature review covering 10 journals, it was found that there is a positive influence of public service quality on public satisfaction in Indonesia. The results of this literature review conclude that there is a significant relationship between the quality of public services and the level of public satisfaction with a significance level of ρ<0.05.